ABOUT INTERRELATION OF CONCEPTS: DISCIPLINE OF LABOUR AND DISCIPLINARY RESPONSIBILITY (HISTORICAL AND LEGAL ASPECT) - Indira Abdulkhakovna Shakirova (Science and Innovation Center Publishing House, 2016)
In the conditions of passing and developing new economic relations in all spheres of the state and public life, political and cultural activity, in realization by citizens of their rights and performing their duties the labour discipline and disciplinary responsibility for its violation are important. The discipline of labour is correct, conscientious, steady and effective performance of duties by employees, and a disciplinary responsibility is a duty to endure adverse consequences for violation of these obligations. The concept of labor discipline is indivisible, uniform (with independence of the Institute of legal regulation of labor discipline in the labor law system) is due to the fact that the content of this concept is seen weaving fundamental requirements of law and morality. The purpose is to show legal and institutional support of labor discipline and a disciplinary responsibility during New Economic Policy. Method or methodology of work: in article modern methods of learning and special methods were used: systematic and comparative law. Results: theoretical propositions and conclusions, characterizing the process of development of labor discipline and disciplinary responsibility institutions in days of new economic policy, can extend and clarify existing concepts of legal responsibility and its types in the history of national law. Application of results: the results may find practical application in law-making activities of governmental institutions and law-enforcement practice.